Sistem Manajemen Mutu Komunikasi Kepada Konsumen Berdasarkan ISO 9001: 2015 Pada Website Sekolah Tinggi Multi Media - Ardian Setio Utomo; Widhihatmini Widhihatmini (Cakrawala - Jurnal Humaniora, 2023)
This study aims to describe the quality management system in the field of communication to consumers based on ISO 9001:2015 on the Multi Media College website. The research method uses descriptive qualitative. Sources of research data are users of the Multi Media College website. Data collection uses the method of observation and documentation. Data analysis was carried out through data collection, data reduction, data presentation, drawing conclusions and verification. To ensure the validity of the data used triangulation method. The results of this study are the communication quality management system to consumers based on ISO 9001: 2015 on the Multi Media High School website including: 1) Providing information related to products and services, 2) withdrawing requests, contracts or orders, including changes thereto, 3) Obtaining consumer feedback related to products and services, including consumer complaints, 4) restrict or control consumer property, and 5) make specific requirements for contingency actions. Recommendations from research results to improve the quality management system in the field of communication to consumers, namely: 1) Providing information related to consumer requirements that can be maintained and maintained properly, 2) Providing information to consumers receiving and answering consumer questions clearly, 3) Providing an effective way to receive complaints from customers and provide answers to them, 4) Provide an effective way to receive feedback from consumers, 5) Maintain an effective channel for sharing information and situations of educational products and services that are not yet in accordance with consumers, 6) establish ways effective for 9 and receive input from consumers in case of contingencies.